Semiparametric dynamic portfolio choice with multiple conditioning variables - Jia Chen; Degui Li; Oliver Linton; Zudi Lu (Centre for Microdata Methods and Practice (cemmap), 2015)
Dynamic portfolio choice has been a central and essential objective for institutional investors in active asset management. In this paper, we study the dynamic portfolio choice depending on multiple conditioning variables, where the number of the conditioning variables can be either fixed or diverging to infinity at certain polynomial rate in comparison with the sample size. We propose a novel data-driven method to estimate the nonparametric optimal portfolio choice, motivated by the model averaging marginal regression approach suggested by Li, Linton and Lu (2014). Specifically, in order to avoid curse of dimensionality associated with the problem and to make it practically implementable, we first estimate the optimal portfolio choice by maximising the conditional utility function for each individual conditioning variable, and then construct the dynamic optimal portfolio choice through the weighted average of the marginal optimal portfolio across all the conditioning variables. Under some mild regularity conditions, we have established the large sample properties for the developed portfolio choice procedure. Both simulation studies and empirical application well demonstrate the performance of the proposed methodology with finite sample and real data.
Keywords: 330; Conditioning variables; kernel smoothing; model averaging; portfolio choice; utility function